The Theory of Changes in Extreme Conditions The Properties and Trends of Changes and Movements The Theory of the Dynamic Structures (International Journal of Engineering and Computer Science, 2015)
Because any physical and chemical effect must be caused by the theory of changes in extreme conditions.So the physics and chemistry are very complicated.There are selfcontradictions and nonSelfconsistents in physics、chemistry、physics and chemistry. The theory of the dynamic structures can solve the selfcontradictions and nonSelf- consistents. The various branches of the science which includes Classical mechanics, classical electromagnetic theory and classical statistical mechanics,Quantum Mechanics , relativity , string theory even the Chemistry,Medical and so on can be united by Energy Structure Theory and the theory of the dynamic structures②.